A Socioeconomic Investigation and Evaluation of Tax Facilities for the Agricultural Sector in Türkiye in the Context of Food Security - Murat Çak; Erdem Yavuz (Maliye Çalışmaları Dergisi)
Countries that cannot provide an adequate food supply due to global warming, climate change, and/or environmental pollution and that have a low import capacity may see their food security suffer. When considering the risk factors regarding the global food supply, one can argue importing to not be an easy or cheap method. Therefore, expanding agriculturally produced products suitable for the new climatic conditions and improving animal breeds so they can adapt to the geographical region can be discussed on a national scale. In order to achieve all of these, governments are recommended to turn to effective agricultural policies in the national context and within the framework of international cooperation. From this point of view, agriculture will be able to benefit from tax expenditure regulations as a fiscal policy instrument. This study analyzes tax facilities for the agricultural sector in Türkiye from a socioeconomic perspective in the context of food security. After examining the relationship between tax expenditures and the GDP from a functional point of view in this context, the study will evaluate tax facilities for the agricultural sector that are handled in the Turkish Tax System in line with Income Tax Law No. 193 and Value Added Tax Law No. 3065 by taking into account animal production statistics and plant production statistics. The study will then discuss possible solutions for the development of agriculture and animal husbandry in Türkiye in the line with the findings.